Imagined communities
1 online resource (395 pages)
Keywords: Imagined Communities: Constructing Collective Identities in Medieval Europe offers a series of studies focusing on the problems of conceptualisation of social group identities, including national, royal, aristocratic, regional, urban, religious, and gendered communities. The geographical focus of the case studies presented in this volume range from Wales and Scotland, to Hungary and Ruthenia, while both narrative and other types of evidence, such as legal texts, are drawn upon. What emerges is how the characteristics and aspirations of communities are exemplified and legitimised through the presentation of the past and an imagined picture of present. By means of its multiple perspectives, this volume offers significant insight into the medieval dynamics of collective mentality and group consciousness. Contributors are Dániel Bagi, Mariusz Bartnicki, Zbigniew Dalewski, Georg Jostkleigrewe, Bartosz Klusek, Paweł Kras, Wojciech Michalski, Martin Nodl, Andrzej Pleszczyński, Euryn Rhys Roberts, Stanisław Rosik, Joanna Sobiesiak, Karol Szejgiec, Michał Tomaszek, Tomasz Tarczyński, Przemysław Tyszka, Tatiana Vilkul, and Przemysław Wiszewski.